PWE-064 Bone density assessment in chronic pancreatitis (CP) : are we screening our patients appropriately?. (June 2019) - Awadelkarim, Bidour; Majumdar, Debasis; Morrison, Charlotte; Tan, JW; Mitra, Vikramjit
Abstract : Patients with CP are at increased risk of low bone density because of multiple factor including malabsorption of vitamin D and calcium, poor diet, alcoholism and smoking [1].Recent NICE guidelines recommend offering bone density assessment to all patients with CP every 2 years [2] Aims and methods: A retrospective audit was carried out to investigate the incidence of bone density abnormality in all patients diagnosed with chronic pancreatitis between September 2014 and April 2018 in our organisation. Data was collected on patient demographics, social history, DEXA scan assessment and laboratory investigations. Results: 123 patients [median age 62 years, male-female ratio 1.7:1] were diagnosed with CP during this period. The aetiology of CP were as follows: alcohol 16.9% ( n=26), smoking 4.8% ( n=6), smoking and alcohol combined 40.6% ( n=50 ), gallstone disease 7.3% (n=9), hereditary pancreatitis 1.6% ( n=2 )and idiopathic in 23.5% ( n=29). 60 (48.8%) patients underwent a baseline DEXA scan [23.3% (n=13) had normal bone density, 35% (n=21) had osteopenia and 41.7% (n=25) had osteoporosis]. One (0.8%) patient had an established diagnosis of osteoporosis prior to presentation and did not undergo a DEXA scan. Serum biochemistry levels including PTH, vitamin D and calcium levels in patients who underwent DEXA scans are summarized in the table enclosed: Conclusion: In our study only 50% of patients underwent investigation for bone density measurement. There was a significantly high (76.7%) incidence of bone density abnormality in patients who underwent DEXA scan highlighting the importance of this test in the long term management of CP patients. Following this audit, emphasis has been placed on DEXA scan assessment in all CP patients in our trust with plans for a re-audit in a year's time. Reference: High prevalence of osteoporosis in patients with chronic pancreatitis: A systematic review and meta-analysis. Duggan S.N., Smyth N.D., Murphy A., MacNaughton D., O'Keefe S.J.D., Conlon K.C. ( 2014) Clinical Gastroenterology and Hepatology, 12 (2), pp. 219–228. Guidelines, N. ( 2018). Pancreatitis | Guidance and guidelines | NICE. [online] Nice.org.uk. Available at: https://www.nice.org.uk/guidance/ng104